STIE Fest Personal Branding Sekolah Tinggi Ilmu Ekonomi Bima Dimedia Digital - Muniarty, Puji; Rimawan, M; Ovriyadin, Ovriyadin (Pakis Journal Institute, 2025)
Competition between universities is getting tighter, both at national and international levels, covering academic aspects, reputation, innovation, and funding. To stay relevant in the digital era, universities must adapt and improve quality, utilizing social media as a means of communication and personal branding. In addition, through community service, institutions can apply science, technology, and art to provide real benefits. Community service uses a participatory method that involves the role of the STIE Bima academic community. in collaboration with the Bima City Hospital and the Bima Regency BNN with stages of preparation, implementation and evaluation. STIE Fest emphasizes the personal branding of universities in community service as an effort to build image and reputation through social contribution. This can be achieved by demonstrating academic expertise, creating useful innovations, and playing an active role in community empowerment. This approach increases public trust and attracts the interest of prospective students, industry partners, and government support, while reflecting a commitment to social development and sustainability.